The National Question in Theoretical Heritage of Al. Miasnikyan - Melkumyan, Arpine (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
The national question was and still remains one of the unsolved problems on a global scale. It was much more vexed in Russia in the early 20th century, when Russian Empire turned into a community of more than one hundred nations, each of which put forward their demands, which often overlap with the requirements of other nations, leading to sharp ethnic conflicts. In the early 20th century this issue was no less acute and urgent in the Caucasus that gave rise to many disputes regarding solutions to the problem put forward by different ideologies and representatives of many social and political trends. This article is an attempt to present the point of view of prominent Armenian political figure of the early 20th century, Marxist theoretician Al. Miasnikyan regarding the national question comparing it with other theorists’ decisions opposing social and political trends.